Peningkatan Kualitas Pelet Tandan Kosong Kelapa Sawit melalui Torefaksi Menggunakan Reaktor Counter-Flow Multi Baffle (COMB) - Wahyu Hidayat; Irma Thya Rani; Tri Yulianto; Indra Gumay Febryano; Dewi Agustina Iryani; Udin Hasanudin; Sihyun Lee; Sangdo Kim; Jiho Yoo; Agus Haryanto (Jurnal Rekayasa Proses, 2020)
Oil palm (Elaeis guineensis) empty fruit bunches (EFB) have not been utilized optimally. Currently, it is considered as a resource with low economic value. This biomass can be converted into bioenergy through a torrefaction process. Torrefaction is a mild pyrolysis at temperatures ranging between 200 and 300 °C, and it is generally performed under an inert atmosphere. The objective of this study was to evaluate the effects of torrefaction using Counter-Flow Multi Baffle (COMB) on the properties of oil palm EFB pellets. Torrefaction was conducted at 280 °C temperature with a residence time of 4 minutes. The results showed a decrease in the equilibrium moisture content and an increase in hydrophobicity after torrefaction using the COMB reactor. The change in the hygroscopic property could make the oil palm EFB pellet more stable against chemical oxidation and microbial degradation, hence self-heating and auto-ignition during storage could be prevented. The heating value of biomass increased after torrefaction. Torrefaction with the COMB reactor resulted in a heating value of 17.90 MJ/kg, which is comparable with the results of oxidative torrefaction (with longer residence time) of 18.28 MJ/kg. The results suggested that torrefaction using the COMB reactor could provide a great improvement in the quality of the bioenergetic properties of oil palm EFB pellets. However, the high ash content of the EFB pellets implied that the EFB pellets suitable for a small-scale application, but not yet for cofiring in power plants or as a feedstock for gasification.Keywords: Counter-Flow Multi Baffle; oil palm empty fruit bunches; renewable; torrefactionA B S T R A KTandan kosong kelapa sawit (Elaeis guineensis) belum dimanfaatkan secara optimal. Saat ini bahan tersebut masih dianggap sebagai sumber daya bernilai ekonomi rendah. Tandan kosong kelapa sawit (TKKS) dapat dikonversi menjadi bioenergi melalui proses torefaksi. Torefaksi merupakan proses pirolisis ringan pada suhu berkisar antara 200 dan 300 °C dan umumnya dilakukan di bawah kondisi inert. Penelitian ini bertujuan untuk mengetahui pengaruh torefaksi dengan reaktor Counter-Flow Multi Baffle (COMB) terhadap sifat-sifat pelet TKKS. Torefaksi dilakukan pada suhu 280 °C dengan waktu tinggal 4 menit. Hasil penelitian menunjukkan bahwa torefaksi menyebabkan penurunan kadar air kesetimbangan dan menjadi hidrofobik setelah torefaksi dengan reaktor COMB. Perbaikan sifat higroskopis dapat membuat pelet TKKS lebih stabil terhadap oksidasi kimia dan degradasi mikroba, sehingga pemanasan sendiri dan pembakaran spontan selama penyimpanan dapat dicegah. Nilai kalor biomassa meningkat setelah torefaksi. Torefaksi dengan reaktor COMB menghasilkan nilai kalor 17,90 MJ/kg, yang sebanding dengan hasil torefaksi oksidatif dengan waktu tinggal lebih lama, sebesar 18,28 MJ/kg. Hasil penelitian menunjukkan bahwa torefaksi dengan reaktor COMB dapat meningkatkan kualitas energi pelet TKKS. Tetapi pelet TKKS masih memiliki kadar abu yang tinggi sehingga biomassa hasil torefaksi belum sesuai untuk cofiring di pembangkit listrik atau sebagai bahan baku untuk gasifikasi.Kata kunci: Counter-Flow Multi Baffle; tandan kosong kelapa sawit; terbarukan; torefaksi